Semantic Relations in a Categorical Verbal Fluency Test: An Exploratory Investigation in Mild Cognitive Impairment - Quaranta, Davide; Piccininni, Chiara; Caprara, Alessia; Malandrino, Alessia; Gainotti, Guido; Marra, Camillo (Frontiers in Psychology, 2019)
Categorical verbal fluency tests are commonly used to assess the integrity of semantic memory in individuals with brain damage. Patients with Dementia of the Alzheimer Type display a reduced output on categorical verbal fluency tests, and a similar pattern has been reported in amnesic Mild Cognitive Impairment (aMCI). The aims of the present study were to assess if the semantic relations between lexical entries produced on a categorical fluency test using the semantic categories ‘birds’ and ‘pieces of furniture’ was different between healthy persons and individuals with aMCI and if this difference was more pronounced in individuals who converted to dementia during a three years follow-up period. Methods Thirty-four individuals affected by aMCI and 29 matched healthy persons were recruited. The aMCI individuals were regularly followed-up and during the follow-up period, 10 of them converted to Dementia (aMCI-conv). Two measures assessing semantic relations between consecutively produced couples of words (Path length and Extended Gloss Overlap) were obtained from Wordnet database. Results The word couples analyzed were 498 in healthy individuals (birds: 262; pieces of furniture: 236) and 395 in aMCI individuals (birds: 174; pieces of furniture: 221). Path length was lower in aMCI-conv than in healthy individuals (p=0.035) but no differences between aMCI-stable and healthy individuals nor between aMCI-stable and aMCI-conv was found. The ANOVA for lexical entries belonging to the “birds” category showed a significant effect of group (F=5.630; p=0.004); the post-hoc analysis showed a significant difference between HP and aMCI-conv (p=0.003); as for the “pieces of furniture” category, the ANOVA showed a significant effect of group (F=4.107; p=0.017), while the post-hoc test showed a significant difference between aMCI-conv and healthy individuals (p=0.049) and aMCI-conv and aMCI-stable (p=0.001). Discussion Individuals with aMCI who convert to dementia show a deterioration in the semantic relations between lexical entries consecutively produced on a categorical verbal fluency tests. This phenomenon may be interpreted as a marker of a very early disruption of semantic memory.